2007
DOI: 10.1038/sj.jid.5700502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UVB on E Prostanoid Receptor Expression in Murine Skin

Abstract: Prostaglandin E2 (PGE2) upregulation in response to UV light exposure is a significant factor in the development of non-melanoma skin cancer. It is known that PGE2 signals via the E prostanoid receptors, EP1-4, but the role that each receptor plays in skin carcinogenesis is unclear. Immunohistochemical analysis of EP receptor staining in unirradiated and UVB-exposed SKH-1 mouse skin demonstrated the localization of EP1 and EP2 to the plasma membrane of differentiated epidermal keratinocytes. In contrast, the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 37 publications
1
46
0
1
Order By: Relevance
“…All of the known receptors, including EP1 and EP2, are expressed in mouse skin and several have been directly linked to UVB-and phorbol ester-induced skin inflammation and carcinogenesis (Thompson et al, 2001;Sung et al, 2006;Brouxhon et al, 2007;Chun et al, 2007). Thus, UVB has previously been reported to stimulate expression of EP1, EP2 and EP4 in mouse skin, but to reduce expression of EP3 (Tober et al, 2007). Moreover, modulating EP receptor expression or activity using genetic and pharmacological approaches has demonstrated that EP1, EP2 and/ or EP4 are critical mediators of the actions of UV light in the skin (Tober et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the known receptors, including EP1 and EP2, are expressed in mouse skin and several have been directly linked to UVB-and phorbol ester-induced skin inflammation and carcinogenesis (Thompson et al, 2001;Sung et al, 2006;Brouxhon et al, 2007;Chun et al, 2007). Thus, UVB has previously been reported to stimulate expression of EP1, EP2 and EP4 in mouse skin, but to reduce expression of EP3 (Tober et al, 2007). Moreover, modulating EP receptor expression or activity using genetic and pharmacological approaches has demonstrated that EP1, EP2 and/ or EP4 are critical mediators of the actions of UV light in the skin (Tober et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Also of note was our observation that EP1 and EP2 relative mRNA levels increased at intermediate doses of UVB (10 and/or 15 mJ/cm 2 ), suggesting that undifferentiated cells were more responsive to UVB than differentiated cells in this parameter. Recent studies using techniques in immunohistochemistry have shown that these receptors are localized in suprabasal keratinocytes in mouse skin (Tober et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The effects of prostaglandins and the cross talk between prostaglandin receptors and their signaling intermediates are of intense interest because of the diverse effects of prostaglandins on cell growth, differentiation and carcinogenesis [3,38,[41][42][43]. While the effects of PGE 2 on epidermal keratinocytes are reasonably well understood [1,[43][44][45], there has been much less investigation in the effects of PGE 2 on human melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In murine and human skin EP 3 receptor expression is localized to the basal layer of the epidermis within keratinocytes [37,38]. To co-localize EP 3 receptor expression in melanocytes, contiguous skin sections were stained with the melanocyte specific antibody Melan-a and with antibodies to EP 3 .…”
Section: Melanocytes Express the Ep 3 Receptor In Skin In Vivomentioning
confidence: 99%
See 1 more Smart Citation